Reflections on the medium of instruction for ethnic minorities in Xinjiang: the case of bilingual schools in Urumqi - Zhang, Qi; Yang, Ting (International journal of bilingual education and bilingualism, 2021)
The medium of instruction (MoI) is regulated in the bilingual education of Xinjiang Uyghur Autonomous Region in two ways. One requires most school subjects to be taught through Mandarin, whereas the other demands that all subjects be delivered with Mandarin as the MoI. A field trip to the capital city, Urumqi, was conducted in 2017 to investigate the implementation of the MoI as stated in the policy. This paper first outlines the history of bilingual education in the region, with a focus on Chinese language education. It then investigates the change of MoI from the ethnic minority language to Mandarin Chinese. The two current modes of bilingual education in Xinjiang are also discussed in detail. The paper further examines the regulations on MoI through interviews with students and teachers from four Urumqi schools. Their understanding of the regulations on MoI usage demonstrates the difficulties of implementing such a policy, one initially proposed with good intentions. Through a thorough examination of official documents as well as interview data, this study shows the discrepancies between national and current regional policies, between planned aim and in-class practice, and between the transitional and balanced types of bilingual education.